The Effect of Promotion of Vessel Crew Vacancies on the Process of Changing Ship Crews at PT Jasindo Duta Segara - Sudiono Sudiono; Desamen Simatupang; Rosmayana Rosmayana; Ahmed Syah Rizan (Dinasti International Journal of Education Management And Social Science, 2022)
Crew Manning Agency is a division that only takes care of crew for ship owners overseas. PT. Jasindo Duta Segara uses International Safety Management (ISM) which aims to be the "Best Crew Supplying Agent in the World" to meet the expectations of the company and crew perfectly. PT. Jasindo Duta Segara will not let owner or crew calls go unanswered. Don't let the owner be served without commitment and don't let the crew fail in their performance. Before joining PT. Jasindo Duta Segara, the crew made a selection at the company using various tests such as: academic, psychological tests, marlin tests, in order to determine the ability of ship crews who want to join PT. Jasindo Duta Segara. The process of changing the crew is very influential in terms of promotion and wages of ship crews. The crew on duty on one ship are Master, Chief Officer, Second Officer, Third Officer, Bosun, Able Seaman, Ordinary Seaman, Chief engineer, First Engineer, Second Engineer, Third Engineer, Oiler No. I, Oiler II, Waper, Chief Cook, and Mass Man. All of these crews are involved in the crew change process in which the promotion of crew vacancies affects the crew change process, in this case resulting in a lack of promotion of crew vacancies that are widely spread through the media and an inconsistency in the crew change process which can disrupt and hinder ship operational activities so as not to eat up the crew. longer time.